Bioinformatics a practical guide to NCBI databases and sequence alignments - Hamid, Ismail D.; National Center for Biotechnology Information (U.S.) (Boca Raton : Chapman & Hall/CRC, 2021)
Bioinformatics: A Practical Guide to NCBI Databases and Sequence Alignments provides the basics of bioinformatics and in-depth coverage of NCBI databases, sequence alignment, and NCBI Sequence Local Alignment Search Tool (BLAST). As bioinformatics has become essential for life sciences, the book has been written specifically to address the need of a large audience including undergraduates, graduates, researchers, healthcare professionals, and bioinformatics professors who need to use the NCBI databases, retrieve data from them, and use BLAST to find evolutionarily related sequences, sequence annotation, construction of phylogenetic tree, and the conservative domain of a protein, to name just a few. Technical details of alignment algorithms are explained with a minimum use of mathematical formulas and with graphical illustrations. Key Features Provides readers with the most-used bioinformatics knowledge of bioinformatics databases and alignments including both theory and application via illustrations and worked examples. Discusses the use of Windows Command Prompt, Linux shell, R, and Python for both Entrez databases and BLAST. The companion website contains tutorials, R and Python codes, instructor materials including slides, exercises, and problems for students. This is the ideal textbook for bioinformatics courses taken by students of life sciences and for researchers wishing to develop their knowledge of bioinformatics to facilitate their own research.
OCLC-licensed vendor bibliographic record.
Keywords: SCIENCE / Life Sciences / Biology / Molecular Biology; SCIENCE / Biotechnology; Bioinformatics